Perioperative Use of Erythromycin Reduces Cognitive Decline After Coronary Artery Bypass Grafting Surgery: A Pilot Study. Issue 5 (September 2017) - Thomaidou, Evanthia; Argiriadou, Helena; Vretzakis, Georgios; Megari, Kalliopi; Taskos, Nikolaos; Chatzigeorgiou, Georgios; Anastasiadis, Kyriakos
Abstract : Objectives: Adverse neurologic outcome can be a debilitating complication after cardiac surgery. The aim of this study was to investigate the potential neuroprotective action of erythromycin, a well known antibiotic agent, regarding postoperative cognitive decline in patients undergoing cardiac surgery. Methods: Forty patients scheduled for elective coronary artery bypass grafting surgery were prospectively randomly assigned in 2 groups: the erythromycin group (n = 19) who received erythromycin at a dose of 25 mg/kg before and after surgery and the control group (n = 21) who did not receive it. All patients were monitored with near-infrared spectroscopy during the operation. Interleukin (IL) 1 and IL-6 as inflammatory markers and tau protein as a marker of brain injury were measured before and after surgery. Neurocognitive assessment was performed before surgery, on the day of discharge, and at 3 months postoperatively. Results: Both groups were comparable in terms of demographic and clinical data. Patients who took erythromycin presented with significantly better cognitive performance before discharge and 3 months after surgery. No significant differences between the 2 groups referring to IL-1 and IL-6 values were detected. Tau serum values were lower in the erythromycin group after surgery. Conclusions: Erythromycin administration attenuates cerebral damage and postoperative cognitive decline after coronary artery bypass grafting surgery. Trial registration: The study was retrospectively registered at ClinicalTrials.gov (NCT01274754). Study start day: November 2008.